PEMBERDAYAAN IBU-IBU PKK DALAM MENGELOLA SAMPAH PLASTIK MELALUI PELATIHAN PEMBUATAN ECOBRICK DI DESA SUMBERJERUK, KECAMATAN KALISAT, KABUPATEN JEMBER - Himmatul Khasanah; Nur Widodo; Fatma Lailatul Jannah; Andin Maulidya Priyambada; Dwi Robiul Riskiyah; Dian Setyo Ningrum; Yola Amalia; Annisa Ilman Nafia (Bajang Institute, 2024)
Plastic is the most popular and most widely used material as a raw material for making component objects such as food wrappers to automotives. Every day, humans produce plastic waste to meet their daily needs. The high amount of plastic waste produced can cause environmental pollution because plastic waste takes 10-100 years to decompose. One way to manage plastic waste into useful objects is to make ecobricks. Ecobrick is a way of handling plastic waste by tightly packing plastic into plastic bottles. Community empowerment in dealing with plastic waste is carried out through ecobrick making training for PKK women in Sumberjeruk Village, Kalisat District, Jember Regency. The long-term goal of this ecobrick training is to reduce plastic waste, recycle plastic waste, and community independence in the economic field as a new business opportunity to make a product that has high selling power. Based on the results of the ecobrick-making training activities, it can be seen that PKK women can make plant pots from ecobrick. In this training activity it is hoped that the community will not only be able to form ecobricks into pots but can also make other forms and can be used as new business opportunities for the community. Utilization of household waste for materials for making ecobrick can be useful in reducing the amount of waste in Sumberjeruk Village and can foster community creativity, especially mothers in Sumberjeruk Village by paying attention to the surrounding environment. In addition, the use of household waste in the manufacture of ecobricks can overcome the dangers of waste for the environment